2016
DOI: 10.1111/tpj.13195
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a small protein domain present in all plant lineages that confers high prephenate dehydratase activity

Abstract: SUMMARYL-Phenylalanine serves as a building block for the biosynthesis of proteins, but also as a precursor for a wide range of plant-derived compounds essential for plants and animals. Plants can synthesize Phe within the plastids using arogenate as a precursor; however, an alternative pathway using phenylpyruvate as an intermediate, described for most microorganisms, has recently been proposed. The functionality of this pathway requires the existence of enzymes with prephenate dehydratase (PDT) activity (EC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 57 publications
3
41
0
Order By: Relevance
“…The new study provides an in-depth analysis of the localization of the six Arabidopsis ADT isoforms, all of which are targeted, by virtue of a transit peptide, to the stroma and stromules of chloroplasts. This extends previous reports on the presence of these six proteins in chloroplasts, as also reported for four ADTs from Pinus pinaster (Rippert et al , 2009; El-Azaz et al , 2016). Bross et al now show that two of the isoforms have additional localizations that point to non-catalytic functions.…”
Section: A New Dimension To Moonlightingsupporting
confidence: 91%
See 1 more Smart Citation
“…The new study provides an in-depth analysis of the localization of the six Arabidopsis ADT isoforms, all of which are targeted, by virtue of a transit peptide, to the stroma and stromules of chloroplasts. This extends previous reports on the presence of these six proteins in chloroplasts, as also reported for four ADTs from Pinus pinaster (Rippert et al , 2009; El-Azaz et al , 2016). Bross et al now show that two of the isoforms have additional localizations that point to non-catalytic functions.…”
Section: A New Dimension To Moonlightingsupporting
confidence: 91%
“…Comprehensive phylogenetic analyses previously classified the plant ADTs into four subgroups that are distinct from the groups encompassing microbial ADTs, including those in the Bacterioidetes/Chlorobi, which represent the closest bacterial homologs (Dornfeld et al , 2014; El-Azaz et al , 2016). This analysis further suggests that plant ADTs diversified following the split of plants and chlorophytes (green algae), with present-day ADTs having evolved from the subfamily I-type enzymes to which ADT2 belongs.…”
Section: A New Dimension To Moonlightingmentioning
confidence: 99%
“…3). Although model microbes, such as E. coli and yeast, only have prephenate dehydratase (PDT) and dehydrogenase (TyrA p ), some bacteria have ADT and TyrA a enzymes, which likely evolved through enzyme neofunctionalization of PDT and TyrA p , respectively, and switch in their substrate specificity from prephenate to arogenate (136,138,(141)(142)(143)(144)(145)(146). Interestingly, all known plant ADTs are most closely related to those of Chlorobi/Bacteroidetes (137), suggesting that both PPA-AT and ADT enzymes required for the arogenate Phe pathway were transferred from Chlorobi/Bacteroidetes to the common ancestor of green algae and land plants.…”
Section: Alternative Phenylalanine Biosynthetic Pathways For Phenolicmentioning
confidence: 99%
“…The cytosolic CM orthologs are present in all angiosperms, but appear to be absent in gymnosperms, ferns, mosses, and Amborella trichopoda, an early diverged flowering plant (148,150,152). Because plastidic ADT isoforms having PDT activity were found in Pinus pinaster (144), a part of the alternative phenylpyruvate Phe pathway may take place also in the plastids in nonflowering plants (153). Thus, some variations exist in the phenylpyruvate Phe pathway at least for its enzyme subcellular localization among different plant groups.…”
Section: Alternative Phenylalanine Biosynthetic Pathways For Phenolicmentioning
confidence: 99%
“…The development of additional protein functions might be easier than originally anticipated, and can probably occur over a relatively short evolutionary time, as it has been shown that only a few amino acid changes can be sufficient to implement a new function. [36][37][38][39] In fact, even a single amino acid change can be sufficient to alter protein function. For example, a single substitution is enough to alter the substrate specificity of a β-glucosidase, 40 or to introduce new substrate recognition to a cyclic nucleotide phosphodiesterase.…”
Section: Why Do Proteins Moonlight?mentioning
confidence: 99%